Clinical Characteristic and Outcome of COVID-19 Patients Using High Flow Nasal Oxygen in Persahabatan Hospital, Jakarta - Wahyu Soebekti; Feni Fitriani Taufik; Mia Elhidsi (Jurnal Respirologi Indonesia, 2022)
Background: Severe and critical COVID-19 patient need intensive care and even invasive mechanical ventilation. Use of high flow nasal oxygen (HFNO) in acute hypoxemic respiratory failure on non-COVID-19 patient can reduce the need for intubation while in COVID-19 patient the data is still inadequate.Methods: This is a retrospective cohort study in 62 confirmed COVID-19 patient using HFNO and treated at Persahabatan Hospital from March to July 2020. Demographic, clinical and laboratory data before HFNO and vital sign, respiratory index after 24 hours of HFNO was taken from medical record. Results: Majority of patients are men (67%), mean age 57.6 years, comorbidity is mostly hypertension and diabetes. HFNO Success outcome is 45.2%. Statistically significant difference between success and failure group is noted on respiratory rate (24 vs 28.5), pulse rate (88.14 vs 100), oxygen saturation (98 vs 94), PaO2/Fio2 (139.27 vs 73), SpO2/FiO2 (116.98 v 102.78) and ROX index (4.97 vs 3.5). Vital sign and respiratory index measured after 24 hours of HFNO showed statistically significant improvement in success group. Conclusion: HFNO can reduce intubation rate in patient with COVID-19. Vital sign and respiratory index are significantly improved in HFNO success group.